THE EFFECTS OF SOCIAL MEDIA MARKETING ACTIVITIES, PERCEIVED QUALITY, BRAND REPUTATION ON PURCHASE DECISION: THE MEDIATING ROLE OF PERCEIVED VALUE AMONG NESTLÉ PURE LIFE CONSUMERS - Maifa Putri Wulandari; Wulan Purnamasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine and analyze the effects of Social Media Marketing Activities, Perceived Quality, and Brand Reputation on Purchase Decision through Perceived Value as a mediating variable for Nestlé Pure Life products. This research employed a quantitative descriptive approach using a non-probability sampling method. Data were collected through purposive sampling from 120 respondents. The data were analyzed using SmartPLS 4.0. The tests conducted included validity and reliability tests, Outer Model evaluation (convergent validity, discriminant validity, composite reliability, Cronbach’s alpha), Inner Model evaluation (path analysis, R-square, Q-square, F-square, and SRMSR), and hypothesis testing. The results indicate that Social Media Marketing Activities have a positive and significant effect on Perceived Value (β = 0.279; p = 0.001), Perceived Quality has a positive and significant effect on Perceived Value (β = 0.257; p = 0.005), and Brand Reputation has a positive and significant effect on Perceived Value (β = 0.318; p < 0.001). Furthermore, Perceived Value positively and significantly affects Purchase Decision (β = 0.363; p < 0.001). Social Media Marketing Activities (β = 0.178; p = 0.043), Perceived Quality (β = 0.194; p = 0.042), and Brand Reputation (β = 0.161; p = 0.045) also have positive and significant effects on Purchase Decision. In addition, Perceived Value mediates the effects of Social Media Marketing Activities (β = 0.101; p = 0.016), Perceived Quality (β = 0.093; p = 0.031), and Brand Reputation (β = 0.115; p = 0.004) on Purchase Decision.